2011
DOI: 10.1016/j.tiv.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Octyl and dodecyl gallates induce oxidative stress and apoptosis in a melanoma cell line

Abstract: This study investigated the mechanism of cytotoxicity of octyl (G8) and dodecyl (G12) gallates in a murine melanoma cell line (B16F10). For this purpose, several methods to measure cell viability were used to determine if the cytotoxicity induced by these gallates corresponds to a general or an organelle-specific effect. Furthermore, the mechanisms related to apoptosis were examined, by studying the caspase-3 activity, oxidative stress, mitochondrial potential and the expression of anti- or proapoptotic protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…G8 is applied in the food, pharmaceutical, and cosmetic industries due to its antioxidant properties . Its alkyl chain contributes to the increased lipophilicity, affinity, and permeability through the cell plasma membranes . This property has been explored in its antitumor effect on B‐cell leukemia, melanoma, and lymphoma .…”
Section: Introductionmentioning
confidence: 99%
“…G8 is applied in the food, pharmaceutical, and cosmetic industries due to its antioxidant properties . Its alkyl chain contributes to the increased lipophilicity, affinity, and permeability through the cell plasma membranes . This property has been explored in its antitumor effect on B‐cell leukemia, melanoma, and lymphoma .…”
Section: Introductionmentioning
confidence: 99%
“…10,13,[45][46][47] The results of this study suggest that GA and DGA present a hepatoprotective effect against the toxic action promoted by CCl 4 . The results of Table 5 indicate that the effect of GA seems to be dose dependent, while the effect of the DGA is dose-independent.…”
Section: Discussionmentioning
confidence: 53%
“…However, they show changes in these markers when given in animals with tumors or in tumor cells. 10,13,[45][46][47] These results lead us to believe that gallic acid and its derivatives selectively act on damaged cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the chemopreventive and anti-carcinogenic effects of gallic acid and its derivatives in animal tumors or human cancer cell lines [12][13][14]. OG induced apoptosis in tumor cells and showed an anti-proliferative effect on melanoma cells [15]. A recent study also showed that OG induced mitochondrial-mediated apoptosis in the hepatocellular carcinoma cell line [16].…”
Section: Introductionmentioning
confidence: 99%